Beyond Awareness: The Role of Environmental Literacy in Sustainable Fashion Behaviour Among Forestry Students - IS Zamani; Dwi Kartika Asih Hasibuan; Madina Dwi Panuntun; Nurfiah Nurfiah (Universitas Negeri Semarang, 2026)
The fashion industry is rapidly expanding while exerting significant pressure on the environment through carbon emissions, textile waste, water pollution, and deforestation. This study investigates how environmental knowledge influences sustainable fashion behavior among forestry students at Tadulako University. A quantitative survey was conducted with 50 purposively selected students who had received basic environmental education. The data were analyzed using descriptive statistics, Pearson correlation, and multiple regression. Results show that overall environmental knowledge is positively related to sustainable fashion attitudes and behaviors, with correlation strengths ranging from weak to moderate. Multiple regression produced an R² of 0.495, indicating that the independent variables collectively explain nearly half of the variation in sustainable fashion behavior. Among the seven knowledge indicators, the ability to seek and read information on sustainable fashion (X6) emerged as the only significant predictor, strongly linked to practices such as reading garment care labels and upcycling. These findings highlight the critical role of practical, applicable knowledge in fostering sustainable fashion consumption